2017
DOI: 10.5902/1980509827686
|View full text |Cite
|
Sign up to set email alerts
|

Conteúdo De Nutrientes Na Biomassa E Eficiência Nutricional Em Espécies Da Caatinga

Abstract: RESUMOObjetivou-se quantificar o conteúdo de nutrientes nos componentes da biomassa da parte aérea das espécies de maior valor de importância em duas áreas de Caatinga e avaliar a eficiência dessas plantas no uso desses nutrientes. A pesquisa foi realizada na fazenda Itapemirim, no município de Floresta -PE, onde foram estudadas duas áreas de vegetação de Caatinga em fases distintas de sucessão ecológica, apresentando características distintas, uma em estágio de regeneração e outra preservada. Na amostragem fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
5
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 5 publications
1
19
5
9
Order By: Relevance
“…These results were generally higher than the observed by Alves et al (2017), who found P leaf levels ranging from 1.7 to 2.9 g kg -1 in the regeneration area and contents ranging from 1.3 to 2.9 g kg -1 in preserved area. The P levels of this study were also higher than those found by Moura et al (2006a) in the leaf biomass of Mimosa caesalpiniifolia (0.7 g kg -1 of P), as well as those found by Medeiros et al (2008) in 10 Caatinga tree-shrub species, where the contents varied from 1.1 to 3.3 g kg -1 of P. The fragment's soil is rich in available P (Table 1), mainly on the surface, facilitating P absorption and accumulation by the plants, thus explaining the higher levels of P in this study.…”
Section: Nutrient Contents In Leaves Of Forest Speciescontrasting
confidence: 75%
See 3 more Smart Citations
“…These results were generally higher than the observed by Alves et al (2017), who found P leaf levels ranging from 1.7 to 2.9 g kg -1 in the regeneration area and contents ranging from 1.3 to 2.9 g kg -1 in preserved area. The P levels of this study were also higher than those found by Moura et al (2006a) in the leaf biomass of Mimosa caesalpiniifolia (0.7 g kg -1 of P), as well as those found by Medeiros et al (2008) in 10 Caatinga tree-shrub species, where the contents varied from 1.1 to 3.3 g kg -1 of P. The fragment's soil is rich in available P (Table 1), mainly on the surface, facilitating P absorption and accumulation by the plants, thus explaining the higher levels of P in this study.…”
Section: Nutrient Contents In Leaves Of Forest Speciescontrasting
confidence: 75%
“…Moura et al (2006a) affirmed that N was the element, which presented the highest levels in the leaf biomass of the Mimosa caesalpiniifolia legume in their studies with plants of the Fabaceae family in stands located in the forest area region in Pernambuco. In the Caatinga forest, Alves et al (2017) also found the highest levels of N in the leaves of the plants in both preserved area and in regeneration. In studying BFN in native forest species of areas with different regeneration times of the Caatinga, Freitas et al (2015) found higher levels of N in legumes of the Mimosa genus.…”
Section: Nutrient Contents In Leaves Of Forest Speciesmentioning
confidence: 80%
See 2 more Smart Citations
“…En lo que se refiere a la concentración de macronutrientes contenidos en el mantillo, en un estudio similar, Alves et al (2017) observaron que hay variación entre las áreas por él estudiadas y entre los períodos, seco y lluvioso para los nutrientes cuantificados. En el período lluvioso, el nitrógeno presentó un promedio de 13.6 g kg -1 ± 2.7 g kg -1 de mantillo en el área de regeneración y 18.6 g kg -1 ± 3.1 g kg -1 en el área preservada.…”
Section: A-1 --unclassified